Caracterização de aspectos imunológicos em modelo de implantes com discos de esponjas de poliéster-poliuretano em diferentes linhagens de camundongos aplicados a avaliação de candidatos vacinais - Mariana Ferreira Lanna (2022)
The polyester-polyurethane sponge implant has been applied as an important in vivo model for the study of inflammatory processes, as it induces the migration, proliferation and accumulation of inflammatory cells, angiogenesis and extracellular matrix deposition in its trabeculae. The detailed characterization of the immune response in these implants would be useful to identify response patterns supporting the selection of the most appropriate experimental model (mouse strain) and the ideal time post-implant in protocols applied to biomolecules screening. In this study, alterations in histological/morphometric, immunophenotypic and functional features of leukocytes were assessed in sponge implants for Swiss, BALB/c and C57BL/6 mice. A gradual increase of the fibrovascular stroma and a progressive decrease in the leukocytes infiltration, initially composed of polymorphonuclear cells with progressive shift to mononuclear cells at late time points, were observed. Swiss mice presented a more prominent immune response with a late mixed pattern (IL-2/IFN-γ/IL-4/IL-10/IL-17) of cytokine production. BALB/c mice showed an early activation of the innate response with a controlled cytokine profile, while C57BL/6 mice presented an early pro-inflammatory response (IL-6/TNF/IFN-γ) with persistent neutrophilic involvement. The selection of the best days after implant for each strain for the application of this model in a vaccine study were chosen considering criteria such as: lower number of biomarkers with high levels, low recruitment of cytotoxic response, lower production of cytokines and lower connectivity of biomarkers (Day5/Swiss; Day7/BALB/c; Day6/C57BL/6). Therefore, the sponge model was applied to the investigation of vaccine immunological memory, where memory cells were studied in previously immunized animals, improving the understanding of vaccine immunogenicity. In this second phase, in Swiss mice, it was observed in the experimental group (Vaccine and Inoculum - V/I), an increase in the percentage of total leukocytes, dendritic cells and T lymphocytes, both CD3+CD4+ and CD3+CD8+, associated with presence of effector memory (EM) CD3+CD4+ T cells, and a pattern of cytokines represented especially by IL-6, TNF, IFN-γ and IL-17. In BALB/c mice, a higher percentage of total leukocytes, neutrophils and CD3+CD8+ T lymphocytes was observed in the experimental group (V/I), while there was a reduction in the population of macrophages and dendritic cells, in addition to a profile of inflammatory cytokines (IL-6/TNF/IFN-γ). In C57BL/6 mice, the functional analysis revealed a more robust response, mediated by higher levels of cytokines with a mixed activation profile (IL-6, TNF, IFN-γ, IL-10 and IL-17), while, phenotypically, there was a reduction in the population of macrophages and dendritic cells, with an increase in neutrophils and CD3+CD4+ T lymphocytes. The results point out how the genetic background can influence the populations involved in the immune response and indicate that it is possible to use this model to optimize and monitor the innate and adaptive immune responses of vaccine candidates, allowing the study of specific response to the stimulus. In this sense, these results can guide the choice of the most appropriate experimental model (Swiss, BALB/c or C57BL/6) in biomolecules tests, considering that the particularities of each strain of mice influenced the dynamics of the immune response.